Life with the Esquimaux [electronic resource] : a narrative of Arctic experience in search of survivors of Sir John Franklin's expedition from May 29, 1860 to September 13, 1862 - Hall, Charles Francis, 1821-1871. (London : S. Low, Son, and Marston, 1865)
Includes publishers list. Also issued under title: Arctic researches and life among the Esquimaux. "With maps, coloured illustrations, and one hundred wood cuts". Includes index. Electronic reproduction. Mode of access: Internet. 44